DEVELOPMENT OF MEASURES TO ENSURE TRAFFIC SAFETY IN THE CENTER OF FERGANA CITY - Nuriddin Obidov; Foziljon Qodiralaiyev (American Journals Publishing, 2023)
This article describes measures developed to ensure road safety in the central part of the city of Fergana. The development of the automobile factory in our republic, the production of cars, and the ownership of personal cars by the population are the reasons for the daily increase in the number of cars. The rapid increase in the number of cars requires the widening of highways and the design and construction of high-rise buildings to accommodate them.
Keywords: Intersection, center, settlement, device, traffic, security, provision, road, movement.